Motivational correlates of mentally tough behaviours in tennis. Issue 1 (January 2015) - Gucciardi, Daniel F.; Jackson, Ben; Hanton, Sheldon; Reid, Machar
Abstract Objectives The purpose of this study was to examine motivational correlates of mentally tough behaviours among adolescent tennis players. Design Two-phase study, involving the development of an informant-rated measure of mentally tough behaviours, followed by a cross-sectional survey including athlete and parent assessments of study variables. Methods In Phase One, 17 adult, high-performance tennis coaches and 20 athletes participated in focus group interviews. Four scholars with expertise in performance psychology also completed a short, online survey. In Phase Two, a total of 347 adolescent tennis players (nmales = 184; nfemales = 163) aged 12–18 years (M = 13.93, SD = 1.47) and one respective parent took part in this study. An online multisection survey containing dimensions of passion, inspiration, fear of failure, and mentally tough behaviours was completed. Athletes self-reported all motivational variables, whereas parents rated their child solely on mentally tough behaviours. Results Structural equation modelling revealed that harmonious passion (β = .26, p < .01) and frequency of inspiration (β = .32, p < .001) were associated with significantly higher levels of mentally tough behaviours. In contrast, fear of failure (β = −.32, p < .001) and obsessive passion (β = −.15, p < .01) were inversely related to mentally tough behaviours. Inspiration intensity was not significantly associated with mentally tough behaviour (β = .13, p = .21). Conclusions Motivational variables that are dispositional in nature, contextualised and contingent upon features of the environment, and concern one's identity are important considerations for understanding mentally tough behaviours.